The salt thief : Gandhi's heroic march to freedom - Bascomb, Neal (Scholastic Focus, 2024)
"Author Neal Bascomb chronicles Gandhi's arguably most famous, and effective, campaign in his fight for India's independence: the Salt March. This campaign would kickstart the first and biggest nonviolent protest movement the world had ever seen, making history"--